2009
DOI: 10.3390/rs1041273
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Algorithm for Estimating Agricultural and Riparian Evapotranspiration Using MODIS Enhanced Vegetation Index and Ground Measurements of ET. I. Description of Method

Abstract: Abstract:We used the Enhanced Vegetation Index (EVI) from MODIS to scale evapotranspiration (ET actual ) over agricultural and riparian areas along the Lower Colorado River in the southwestern US. Ground measurements of ET actual by alfalfa, saltcedar, cottonwood and arrowweed were expressed as fraction of potential (reference crop) ET o (ET o F) then regressed against EVI scaled between bare soil (0) and full vegetation cover (1.0) (EVI*). EVI* values were calculated based on maximum and minimum EVI values fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 62 publications
(129 reference statements)
0
93
0
Order By: Relevance
“…These problems tend to be minimized in dryland irrigation districts where rainfall is infrequent and 80-90% of applied water is consumed in E veg , see [5]. Stress of crops is minimized due to the provision of irrigation water, and riparian plants are mainly phreatophytes that have a more-or-less constant water supply from the shallow aquifer under the riparian floodplain [16] (also see [17,18]). Furthermore, an estimate of soil evaporation can be obtained separately with the two-source model for estimating ET a , which uses drying curves based on soil type to derive evaporation rates following an irrigation or rain event [19].…”
Section: Applicability Of Vi-et O Methods To Dryland Irrigation Distrmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems tend to be minimized in dryland irrigation districts where rainfall is infrequent and 80-90% of applied water is consumed in E veg , see [5]. Stress of crops is minimized due to the provision of irrigation water, and riparian plants are mainly phreatophytes that have a more-or-less constant water supply from the shallow aquifer under the riparian floodplain [16] (also see [17,18]). Furthermore, an estimate of soil evaporation can be obtained separately with the two-source model for estimating ET a , which uses drying curves based on soil type to derive evaporation rates following an irrigation or rain event [19].…”
Section: Applicability Of Vi-et O Methods To Dryland Irrigation Distrmentioning
confidence: 99%
“…Finally, soil hydraulic properties can constrain ET a by limiting the rate at which the capillary fringe from which phreatophytes extract water can be replenished during the day [30]. Nagler et al [17,18], working at salinized sites on the Lower Colorado River, found that mean ET a across sites could be predicted by VI-ET o methods with a standard error of about 20% across sites, but that ET a at any given site could vary much more due to differences in aquifer and soil properties among sites.…”
Section: Methods Applied To Riparian Vegetationmentioning
confidence: 99%
“…The park contains more than 60 different species, size and type of landscape trees and shrubs with an additional broad coverage of Kikuyu turf grass, which is irrigated using a sprinkler system. Several research studies have successfully developed ET prediction models using VIs for different vegetation covers [19] including shrub lands [20,21], riparian sites [22][23][24][25], and over regional scales with a variety of land covers/land uses of grasslands to forests [26,27]. NDVI, the most widely used VI, quantifies the vegetation's photosynthetic response to red radiation absorption and near infrared reflectance [28][29][30][31][32][33].…”
Section: Study Areamentioning
confidence: 99%
“…The authors employed a recently published remotely sensed algorithm by Nagler et al [12] using Enhanced Vegetation Index (EVI) from MODIS for ET estimation in Veale Gardens mixed vegetation area. EVI (Equation (3)) was developed as an index to compensate for canopy background noises and topographic variations [6,22].…”
Section: Independent Remotely-sensed Et Estimation In Veale Gardensmentioning
confidence: 99%
“…• empirical methods that involve the use of statistically-derived relationships between ET and vegetation indices such as the normalized difference vegetation index (NDVI) or the enhanced vegetation index (EVI) [20][21][22][23][24][25], • residual methods of surface energy balance (single-and dual-source models) [8,26] which include the Surface Energy Balance Algorithm over Land (SEBAL) [27,28], Surface Energy Balance System (SEBS) [8,29,30] and Mapping EvapoTranspiration at high Resolution with Internalized Calibration (METRIC) [6,31,32], • physically-based methods that involve the application of the combination of Penman-Monteith [7,33,34] and Priestley-Taylor types of equations [35][36][37][38][39], and • Data assimilation methods adjoined to the heat diffusion equation [40] and through the radiometric surface temperature sequences [41].…”
mentioning
confidence: 99%